From the design of brand and trade mark to the certification - Khramova-Baranova, H. L. (History of science and technology, 2014)
In the article the idea of certification and common her understanding are shown from old times. The analysis of literary sources is done, that confirms the necessity of клеймования products a manufacturer for the receipt of her high quality, and also forming of legislative base of certification. A period is lighted up, when the simplest form of certification and producer of products was conceived first began to assert that she conforms to the requirements of the generally accepted standard.